2018
DOI: 10.1039/c8ay01386a
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic frameworks and electron mediator-based open circuit potential biosensor forin vivoelectrochemical measurements

Abstract: Schematic illustration of the structure of GOD/DMFc/COF-LZU1/CFMEs and the analytical principles of OCPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Su et al reported a COF‐based electronic media mediated open circuit potential biosensor (OCPS) consisting of a carbon fiber microelectrode (CFME) and an Ag/AgCl reference microelectrode for glucose detection . The authors used the previously reported 2D COF‐LZU1, prepared by the condensation of 1,3,5‐triformylbenzene and 1,4‐diaminobenzene for electrode construction.…”
Section: Enzyme Immobilization Into Covalent Organic Frameworkmentioning
confidence: 99%
“…Su et al reported a COF‐based electronic media mediated open circuit potential biosensor (OCPS) consisting of a carbon fiber microelectrode (CFME) and an Ag/AgCl reference microelectrode for glucose detection . The authors used the previously reported 2D COF‐LZU1, prepared by the condensation of 1,3,5‐triformylbenzene and 1,4‐diaminobenzene for electrode construction.…”
Section: Enzyme Immobilization Into Covalent Organic Frameworkmentioning
confidence: 99%
“…Through design, the good matched pore size could impede the aggregation of enzymes and facilitate the rapid transportation of reagents at the same time [ 29 ]. There are also specific sites on the interface for weak interaction or covalent binding [ 30 , 31 ], so that the immobilization process varies with a practical need [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through design, the good matched pore size could impede the aggregation of enzymes and facilitate the rapid transportation of reagents at the same time. 29 There are also speci c sites on the interface for weak interaction or covalent binding, 30,31 so that the immobilization process varies with a practical need. 32 Since Kandambeth et al reported the rst example to utilize COFs for enzyme immobilization, 33 a few COF-based immobilized enzymes are reported for applications, such as the kinetic resolution of secondary alcohols by Sun et al(TPB-DMTP-COF@Lipase PS) 34 and chiral separation by Zhang et al(lysozyme covalently immobilized on COF 1 ).…”
Section: Introductionmentioning
confidence: 99%